Hydrogen fuel cell trucks: Total cost of ownership analysis for the People's Republic of China - Qiong Zhang; Dina Azhgaliyeva (Asian Development Bank Institute (ADBI), 2024)
High cost is a significant barrier to the adoption of hydrogen technology in the transportation sector. Using a comprehensive total cost of ownership (TCO) analysis this study evaluates the economic viability of hydrogen fuel cell trucks (FCT) in 2023 and estimates for 2030, in the People's Republic of China's transportation sector, in comparison to electric and diesel trucks. The model quantifies the economic impact of the inconvenience associated with hydrogen refueling, a critical factor that has been insufficiently addressed in existing literature, on TCO of FCTs. The following key results with policy implications are obtained. First, the price of hydrogen has the largest impact on FCT's TCO, compared to other costs. Second, FCTs have the highest fuel consumption cost, and this gap widens over longer distances due to both poor fuel efficiency and high hydrogen price. Third, travel disutility cost (as a share of TCO) is greater for FCT comparing to electric and diesel tracks. Fourth, TCO of FCTs is greater than electric and diesel trucks, despite generous purchase subsidy in the PRC, however, it is expected that TCO of FCTs will become lower by 2030 given the expected reduction of hydrogen price. Thus, hydrogen price reduction (due to production cost decline or subsidy), and investment in hydrogen refueling infrastructure are expected to reduce FCT TCO. In 2030 TCO of FCT will become competitive with electric and diesel trucks, even without carbon tax.
Keywords: O14; O18; R42; R48; 330; hydrogen; People's Republic of China; electric vehicles (EVs); trucks; transportation; clean transport; total cost of ownership analysis